Responses of pink shrimpFarfantepenaeus brasiliensis(Latreille, 1817) (Penaeoidea) to physico-chemical parameters in a marine protected area: changes in abundance and distribution after 20 years - De Sousa, Aline Nonato [UNESP]; De Almeida, Ariadine Cristine [UNESP]; Hiroki, Katia Aparecida [UNESP]; Bernardo, Camila Hipolito [UNESP]; Bernardes, Veronica Pereira [UNESP]; Fransozo, Adilson [UNESP] (Taylor & Francis Ltd, 2020)
This study analysed the influence of temperature, salinity and sediment texture on the distribution of pink shrimp juveniles (Farfantepenaeus brasiliensis) over a 20-year period. The shrimps were sampled monthly in Fortaleza Bay, north coast of Sao Paulo, Brazil, in November 1988-October 1989 (period 1) and then 20 years later in November 2008-October 2009 (period 2). In period 1 we captured 80 juveniles whereas in period 2 we captured 226. The abundance and distribution ofF. brasiliensisseemed to be modulated by temperature and sediment texture, along with the fishing activity. The management strategies established between the samplings might have been responsible for the higher abundance of juveniles seen during period 2. The strategies included the limitation of fishing effort, regulation of fishing equipment and the establishment of environmental protection areas and temporary fishing ban.
Keywords: Spatial-temporal distribution; sediment; fishery; conservation; Ubatuba